Defeat of Proposition 64 celebration. - Sahl, Ted (photographer):::Creator::::::::::::
Proponents of defeating Proposition 64 at the Billy DeFrank Center: (left-to-right) unidentified man, Terry Christensen, Wiggsy Siversten, Delaine Eastin, and Ken Yeager.